qanda-logo
search-icon
Símbolos
Problema
solution-image
LAS SIGUIENTES OPERACIONES CON CUATRO FACTORES. $kCT/0kD-FEf112$ $2$ (3) $4\right)\left(-2=$ $-4\right)\left(-3\right)\left(1\right)\left(-2\right)=$ $\left(-3\right)\left(4\right)\left(5\right)\left(-4\right)=$ (-1) (2) (5) (2) = $\left(3\right)\left(-3\right)\left(-1\right)\left(-2\right)=$ $-2$ $2\right)$ $\left(4$ $\left(5\right)=$ $6\right)\left(2\right)\left(-1\right)\left(2\right)$ $\left(-3\right)\left(-2\right)\left(-3\right)\left(-2\right)=$ $\left(-2\right)\left(-4\right)\left(1\right)\left(1\right)=$ (8) $2$ $2\left(1$ $\left(4\right)\left(-3\right)\left(-2\right)\left(-2\right)=$ $\left(4\right)\left(5\right)\left(2\right)\left(-1\right)=$
Secundaria
Otra
Búsquedas: 141
Contenido de la pregunta
me ayuda por favor?
Solución
answer-user-profile-image
Profesor de Qanda - JhuamanV
answer-reply-image
Problemas similares